Aggregatilinea lenta gen. nov., sp. nov., a slow-growing, facultatively anaerobic bacterium isolated from subseafloor sediment, and proposal of the new order Aggregatilineales ord. nov. within the class Anaerolineae of the phylum Chloroflexi. Issue 4 (18th February 2019) - Nakahara, Nozomi; Nobu, Masaru K.; Takaki, Yoshihiro; Miyazaki, Masayuki; Tasumi, Eiji; Sakai, Sanae; Ogawara, Miyuki; Yoshida, Naoko; Tamaki, Hideyuki; Yamanaka, Yuko; Katayama, Arata; Yamaguchi, Takashi; et al.
Abstract : A novel slow-growing, facultatively anaerobic, filamentous bacterium, strain MO-CFX2 T, was isolated from a methanogenic microbial community in a continuous-flow bioreactor that was established from subseafloor sediment collected off the Shimokita Peninsula of Japan. Cells were multicellular filamentous, non-motile and Gram-stain-negative. The filaments were generally more than 20 µm (up to approximately 200 µm) long and 0.5–0.6 µm wide. Cells possessed pili-like structures on the cell surface and a multilayer structure in the cytoplasm. Growth of the strain was observed at 20–37 °C (optimum, 30 °C), pH 5.5–8.0 (pH 6.5–7.0), and 0–30 g l −1 NaCl (5 g l −1 NaCl). Under optimum growth conditions, doubling time and maximum cell density were estimated to be approximately 19 days and ~10 5 cells ml −1, respectively. Strain MO-CFX2 T grew chemoorganotrophically on a limited range of organic substrates in anaerobic conditions. The major cellular fatty acids were saturated C16 : 0 (47.9 %) and C18 : 0 (36.9 %), and unsaturated C18 : 1 ω9c (6.0 %) and C16 : 1 ω7 (5.1 %). The G+C content of genomic DNA was 63.2 mol%. 16S rRNA gene-based phylogenetic analysis showed that strain MO-CFX2 T shares a notably low sequence identity with its closest relatives, which were Thermanaerothrix daxensis GNS-1 T and Thermomarinilinea lacunifontana SW7 T (both 85.8 % sequence identity). Based on these phenotypic and genomic properties, we propose the name Aggregatilinea lenta gen. nov., sp. nov. for strain MO-CFX2 T (=KCTC 15625 T, =JCM 32065 T ). In addition, we also propose the associated family and order as Aggregatilineaceae fam. nov. and Aggregatilineales ord. nov., respectively.